Intimacy, passion and commitment as mediators on the effect of self-esteem on subjective well-being - Dichupa, Alexander Paul L. (Animo Repository, 2013)
Numerous articles present an idea that loving ourselves enables us to love others which in turn lead to our own happiness, however there have not been any single empirical research study done in order to validate such claim. Thus, the present study tested a model of Sternberg Triangular theory of Love components as mediators between self-esteem and subjective well-being that may support the idea. Mediation analysis by Baron and Kenny was utilized using sample of 300 emerging and young adults ages 20-40, involved in a romantic relationship during the time of the study. Findings revealed that intimacy is a partial mediator on the effect of self-esteem on subjective well-being for the whole sample. Hence, self-esteem is linked to increase intimacy with their romantic partner that could lead to a relatively higher subjective well-being. Intimacy, passion and commitment in young adults and married individuals partially mediate the effect of self-esteem on subjective well-being. Therefore, young adults and married individuals who have higher self-esteem could increase their levels of intimacy, passion and commitment that would in turn lead to higher subjective well-being. Further discussion on the findings and significance of the result are also presented.